Multiangle photopolarimetric aerosol retrievals in the vicinity of clouds: Synthetic study based on a large eddy simulation. Issue 21 (5th November 2016) - Stap, F. A.; Hasekamp, O. P.; Emde, C.; Röckmann, T.
Abstract: We investigate the effect of cloud contamination and 3‐D radiative transfer effects on aerosol retrievals from multiangle photopolarimetric measurements in the vicinity of clouds. To this end multiangle, multiwavelength photopolarimetric observations are simulated using a 3‐D radiative transfer model for scenes with realistic cloud properties, based on a large eddy simulation. Spatial resolutions of 2 × 2, 4 × 4, and 6 × 6 km 2 have been considered. It is found that a goodness‐of‐fit criterion efficiently filters out cloud contamination. However, it does not filter out all scenes that are affected by 3‐D radiative effects, resulting in small biases in the retrieved aerosol optical thickness (AOT) and single‐scattering albedo (SSA). We also found that measurements at higher spatial resolution (2 × 2 km 2 ) do not result in retrievals closer to clouds compared to measurements at coarser spatial resolutions (4 × 4 and 6 × 6 km 2 ). If cloud parameters are fitted simultaneously with aerosol parameters using a 1‐D radiative transfer model and the Independent Pixel Approximation, more successful retrievals are obtained in partially cloudy scenes and in the vicinity of clouds. This effect is most apparent at 6 × 6 km 2 and only marginal at 2 × 2 km 2 resolution. The retrieved aerosol AOT and SSA from the simultaneous aerosol and cloud retrievals still have a small bias, like the aerosol‐only retrievals. We conclude that in order to substantially improve aerosol retrievals in the vicinity of clouds, a retrieval algorithm is needed that takes into account 3‐D radiative transfer effects. Key Points: Simultaneously fitting cloud and aerosol allows for aerosol retrievals closer to clouds Three‐dimensional effects need to be taken into account to improve aerosol retrievals near clouds